A Study on Digital Images and Their Related Methods: Exploring Various Techniques and Algorithms for Image Processing (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Image Processing is a technique to improve raw images received from cameras placed on satellites, space probes and aircrafts or pictures taken in normal life for various applications. Basically, all image processing operations can be grouped into some techniques Image representation, Image preprocessing , Image enhancement , Image restoration , Image analysis, Image reconstruction, Image data compression. The past deals with initial processing of raw image data to correct for geometric distortion, to standardize the data radiometrically and eliminate noise present in the data. The aim of the information extraction operations is to replace visual analysis of the image data with quantitative techniques for automating the identification of tone in a scene. This involves the analysis of multispectral image data and the application of statistically based decision rules for determining the earth cover identity of each pixel in an image. The objective of categorization process is to classify all pixels in a digital image into one of several earth cover classes or themes. This paper entails the analysis of various image processing techniques and algorithms. In this paper we analyze different types of existing method of image processing techniques.